Gender and other factors influencing the burden of care in relatives of people diagnosed with schizophrenia and schizophrenia spectrum disorders. Issue 4 (2nd October 2018) - Cirici Amell, Roser; Cobo, Jesus; Martí Castanyer, Maria; Giménez Gómez, Nuria
ABSTRACT: Burden of care is a complex construct. A gender approach could help to a further understanding of the process. However, previous publications give us inconclusive data. The aim of this study is to evaluate the impact of gender and other factors in the burden experienced by relatives of people diagnosed with schizophrenia spectrum disorders. A sample of 93 Mediterranean Caucasian caregivers (70% women) of 61 patients (87% men) responded to a structured interview and to the Spanish version of Zarit Burden Interview (ZBI). The ZBI showed a 0.872 Cronbach α-coefficient. The best factorial solution included five main components explaining 62% of the variance. Of caregivers, 89% showed high levels of burden. Burden ZBI scores (from highest to lowest) accounted for: worries about patient's future, strain, interference with privacy, lack of resources and feelings of rejection towards the patient. Global burden was not associated with carer's gender but it was significant with patients' gender ( p = 0.025). There were significant differences in caregiver's gender in items 'Health' ( p = 0.020) and 'Loss of life control' ( p = 0.027). Burden suffered by female patients' caregivers was 13 points higher (95%CI: 2–24%). In conclusion, in our sample, few relatives escaped from emotional distress and patient's gender influenced the results.